The Effect of Strategy Implementation On the Growth of the Training Institutions in Machakos County, Kenya - Mutua, Mutuku Michael; Nzioki, Susan; Kinyili, Jacinta (International Journal of Economics, Commerce and Management, 2019)
The aim of the study was to determine the effect of strategy implementation on the growth of training institutions in Machakos County. The design was a descriptive survey. The target population was the Board of Management, Principals, Teaching staff and Support staff from 6 training institutions within Machakos County. 192 respondents were selected from a population of 368 using stratified random sampling. The data was collected using questionnaires which had closed ended and open ended questions. The study employed both quantitative (descriptive and regression statistics) and qualitative data analysis. The study found that majority of institutions followed Situational Analysis procedure in strategy implementation. Further the study found that inadequacy of Information Systems used to monitor strategy formulation; poor planning; lack of support and poor coordination, and poor communication were challenges of Strategy implementation which affected growth of training institutions. Based on the findings on strategy implementation, it can be recommended that the management should make an effort to improve further on Strategic management in order to raise the level of performance of training institutions. In addition, training institutions which are implementing their strategy formulation should develop effective strategic communication in order to attain their objectives. The training institutions should also give more attention to enhancement of teamwork and human resource management.
Keywords: Strategy implementation; Institutional growth; Training institutions